CRITICAL THEORY AND THE END OF HISTORY THESIS: A COMPARATION - Rifqi Khairul Anam (SOCIAL EDU: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This paper examines the contrasting perspectives of the Frankfurt School and Francis Fukuyama on the direction and purpose of human history. The Frankfurt School, a group of critical theorists, offered a radical critique of modernity and capitalism, arguing that history is a continuous process of struggle and change driven by underlying societal contradictions. They view liberal democracy as a form of domination and advocate for a radical transformation of society. In contrast, Fukuyama's "end of history" thesis posits that liberal democracy represents the final stage of human political evolution, marking the end of ideological conflict. This paper explores the fundamental differences between these two perspectives, particularly their views on history, ideology, and the potential for social change.